2012
DOI: 10.1002/app.36920
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in toughness and heat resistance of poly(lactic acid)/polycarbonate blend through twin‐screw blending: Influence of compatibilizer type

Abstract: The thermal mechanical properties and morphological changes of modified poly(lactic acid) (PLA) and polycarbonate (PC) polymer blends based on the equal weight fraction of each component were investigated. Several blend samples were prepared by melt processing with a twin screw extruder using both poly(butylene succinate-co-lactate) (PBSL) and epoxy (EP) as compatibilizers for the PLA/PC binary system. Differential scanning calorimetry (DSC) of PLA/PBSL and PC/PBSL binary blends showed that individual componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…The results showed that SAN-g-MAH was the most effective compatibilizer [35]. Wang et al [36] also used PC to toughen PLA. Poly (butylene succinate-co-lactate) (PBSL) and epoxy (EP) were used as compatibilizers.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The results showed that SAN-g-MAH was the most effective compatibilizer [35]. Wang et al [36] also used PC to toughen PLA. Poly (butylene succinate-co-lactate) (PBSL) and epoxy (EP) were used as compatibilizers.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…To increase thermal resistance, PLA can be blended with PC. The adhesion between these two polymers is weak due to interfacial tension and weak entanglements [62][63][64].…”
Section: Polylactic Acid (Pla) and Blendsmentioning
confidence: 99%
“…It is known that thermal treatment induces exchange reactions that lead to the formation of copolymers with a final structure that is also affected by parallel decomposition reactions, mainly the loss of carbon dioxide and ethylene carbonate (EC) [64,65]. Therefore, it is predicted that PLA and its blends will have some kind of bonding reaction with PC, weak-to-medium in strength.…”
Section: Polylactic Acid (Pla) and Blendsmentioning
confidence: 99%
“…Generally, it is synthesized through ring-opening polymerization of lactides or direct condensation processes of lactic acid monomers which are derived from the fermentation of sugar feed stocks [1,2]. In the present, PLA is one of the most popular biodegradable polymers due to several excellent reasons; high mechanical strength, renewable product, biocompatibility, fully biodegradation within a few weeks, transparency, gas permeability, and easy processability [3][4][5]. According to these advantages, PLA which can be potentially applied in many fields such as tissue engineering, drug delivery system, automobile, food container, and film packaging becomes a promising and outstanding bio-based material for replacing petroleum-based plastics, e.g., polyolefins (PE and PP), polystyrene (PS), and poly (ethylene terephthalate) (PET) as well [6][7][8].…”
Section: Introductionmentioning
confidence: 99%